Agreement Among 4 Sampling Methods to Identify Respiratory Pathogens in Dairy Calves with Acute Bovine Respiratory Disease. (14th March 2017) - Doyle, D.; Credille, B.; Lehenbauer, T.W.; Berghaus, R.; Aly, S.S.; Champagne, J.; Blanchard, P.; Crossley, B.; Berghaus, L.; Cochran, S.; Woolums, A.
Abstract : Background: Four sampling techniques commonly are used for antemortem identification of pathogens from cattle with bovine respiratory disease (BRD): the nasal swab (NS), guarded nasopharyngeal swab (NPS), bronchoalveolar lavage (BAL), and transtracheal wash (TTW). Agreement among these methods has not been well characterized. Objective: To evaluate agreement among TTW and NS, NPS, or BAL for identification of viral and bacterial pathogens in dairy calves with BRD. Animals: One hundred dairy calves with naturally acquired BRD. Methods: Calves were sampled by all 4 methods. Viral agents were identified by real‐time RT‐PCR, bacteria were identified by aerobic culture, and Mycoplasma bovis ( M. bovis ) isolates were speciated by PCR. Agreement among TTW and NS, NPS, or BAL was evaluated by calculating the kappa statistic and percent positive agreement. McNemar's exact test was used to compare the proportions of positive results. Results: Agreement among TTW and NS, TTW and NPS, and TTW and BAL, was very good for identification of P. multocida, M. haemolytica, and M. bovis . For bovine respiratory syncytial virus (BRSV), agreement with TTW was moderate for NS, good for NPS, and very good for BAL. For bovine coronavirus (BCV), agreement with TTW was moderate for NS and NPS, and good for BAL. McNemar's test was significant only for BCV, indicating that for this pathogen the proportion of positive results from NS and NPS could not be considered comparable to TTW. Conclusions and Clinical Importance: This study provides guidance for veterinarians selecting diagnostic tests for antemortem identification of pathogens associated with BRD.